Los Hechos y su interpretación - Padilla Moreno, Juan (Revista de Teoria da História, 2021)
This paper tries to cast light on the relation between historical facts and their interpretations. The thesis maintained is that facts and interpretations are inseparable but at the same time can’t be mixed up, because they are correlative: the sense of both terms depends on their mutual relation. This correlation can be observed even in the ethical aspects of history. The thesis is illustrated with some examples. Se trata de arrojar claridad sobre la cuestión de la relación entre los hechos históricos y sus interpretaciones. Se mantiene la tesis de que unos y otras no pueden ni separarse ni confundirse porque son correlativos: su sentido depende de la relación que mantienen entre sí. Dicha correlación se puede observar incluso en el aspecto ético. Se ilustra la tesis con algunos ejemplos.